077 Osteoporosis and bisphosphonate's use associated with reduced progression of calcific aortic stenosis: retrospective observational single centre study. (16th May 2012) - Saeed, Y; Lythgoe, D; Garg, P; Chuah, S
Abstract : Purpose: Progression of Aortic Stenosis (AS) has been subject of much debate in the recent past with studies evaluating effects of statin therapy. Little is known about the factors that affect progression of AS. Recently there is a growing interest in the field of Bone modifiers reducing progression of AS. In this study we aim to study the effects of osteoporosis and bisphosphonate on progression of calcific AS. Methods: Retrospective electronic case notes of patients who had diagnosis of AS with at least two echocardiogram between 2005 and 2009 were studied. Exclusion criteria includes diagnosis of Rheumatic heart disease, bicuspid aortic valve and other significant valvular pathology. Demographics, AS severity, statin use. Peak velocity, Mean gradient, Left ventricular function were recorded. Rate of change of mean gradient (mm Hg/year) and Peak velocity (m/s/year) were then calculated from this data. Previous studies evaluating natural history of progression of AS shown that on average the rate of progression of Peak velocity across aortic valve is 0.24 m/s/year (m/s/yr). We have used this value as cut-off to identify patients in which AS has progressed. Electronic case notes were reviewed to identify osteoporotic patients on bisphosphonate during the study period. Results: N 103 Male 13 Mean Age 79.89 SD ±10.29. Patient are then divided into two groups based on diagnosis of osteoporosis (Bisphosphonate group) and Control (Non-bisphosphonate). No statistically significant differences was found in between groups in terms of demographics. Please refer to Abstract 077 table 1 . Differences in rate of change of Peak velocity (m/s/yr) and mean gradient (mm Hg/yr) between the bisphosphonate and non-bisphosphonate groups were assessed using linear regression with statin status and left ventricular function included as covariates. Differences in rate of change of velocity of 0.13 m/s/year (95% CI 0.01 to 0.26), p=0.034 and in mean gradient of 2.59 m/s/year (95% CI 0.75 to 4.45), p=0.006 were demonstrated. Patient group, statin status, severity of AS and left ventricular function were included as independent variables in a logistic regression model used to discriminate between "progressors" (defined as a rate of change of velocity of >0.24 m/s/year) and "non-progressors" (≤0.24 m/s/year). The OR associated with being a progressor (Non-bisphosphonate/bisphonate group) was 4.83 (95% CI 1.63 to 14.32), p=0.006 or equivalently the RR was 2.96 (if the patient is not treated with bisphosphonates). Conclusion: Our study has shown that Osteoporotic patients on Bisphosphonate have significantly decreased progression of AS. Whether this result was due to bone metabolism associated with either osteoporosis and/or bisphosphonate use needs to be clarified further in randomised control trials.